2014
DOI: 10.1371/journal.pone.0106364
|View full text |Cite
|
Sign up to set email alerts
|

Novel Apigenin Based Small Molecule that Targets Snake Venom Metalloproteases

Abstract: The classical antivenom therapy has appreciably reduced snakebite mortality rate and thus is the only savior drug available. Unfortunately, it considerably fails to shield the viper bite complications like hemorrhage, local tissue degradation and necrosis responsible for severe morbidity. Moreover, the therapy is also tagged with limitations including anaphylaxis, serum sickness and poor availability. Over the last decade, snake venom metalloproteases (SVMPs) are reported to be the primary component responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…According to the literature, the presence of flavonoids could be especially interesting in antiophidic plants since these compounds are able to promote strong hydrogen bonds with amides of protein chains and exhibit metal chelating activity, as well as present potent anti-inflammatory and antioxidant activities [28, 36]. In fact, several studies show that flavonoids (such as apigenin, moreloflavone, quercetin, luteolin, among others) have the ability to inhibit SVMPs, PLA 2 s, and hyaluronidases purified from snake venoms, showing great inhibitory effects against envenoming-induced local effects [60, 61, 62, 63, 64, 65]. So, the great amounts of flavonoids in raw materials and extracts of K .…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, the presence of flavonoids could be especially interesting in antiophidic plants since these compounds are able to promote strong hydrogen bonds with amides of protein chains and exhibit metal chelating activity, as well as present potent anti-inflammatory and antioxidant activities [28, 36]. In fact, several studies show that flavonoids (such as apigenin, moreloflavone, quercetin, luteolin, among others) have the ability to inhibit SVMPs, PLA 2 s, and hyaluronidases purified from snake venoms, showing great inhibitory effects against envenoming-induced local effects [60, 61, 62, 63, 64, 65]. So, the great amounts of flavonoids in raw materials and extracts of K .…”
Section: Resultsmentioning
confidence: 99%
“…Later, diverse studies demonstrated the ability of these compounds to inhibit MMP-1 [ 32 ], MMP-2 and MMP-9 [ 33 ], among others. Similary, gallocatechin and apigenin derivatives have been shown to antagonize the hemorrhagic activity of venoms and purified toxins from different Viperidae venoms [ 17 , 34 ]. Nonetheless, thus far, the most active recognized SVMP inhibitor is the peptidomimetic Batimastat, a compound that inhibits BaP1 proteolytic activity on biotinylated casein, with an IC value of 80 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin has been detected in the molecular library of ABS in this present study. Apigenin has inhibitory effects against the snake venom metalloproteases, the main component accountable for the hemorrhage and tissue degradation at the bitten site [ 59 ]. Therefore, the already established antihemorrhagic efficacy of ABS and its apigenin content shall be searched in future toxicological experiments.…”
Section: Discussionmentioning
confidence: 99%